The `need for speed': Towards circular disruption—What it is, how to make it happen and how to know it's happening - Fenna Blomsma; Thomas Bauwens; Ilka Weissbrod; Julian Kirchherr (Business Strategy and the Environment, 2022)
The environmental, social and economic limits and shortcomings of the current linear model of production and consumption highlight the necessity of a rapid transition towards a sustainable paradigm. The concept of a circular economy has recently gained traction among scholars, policy-makers and businesses as a promising alternative. Yet our understanding of how to speed up the systemic transition from a linear economy paradigm towards a circular economy paradigm is lacking. In this paper, we address this research gap by introducing the concept of `circular disruption' and by describing how such a disruption may unfold. To do so, we build on S-curve thinking and the concept of panarchy. Based on the resulting synthesis, we propose three phases that constitute the core of the disruption process: (1) the release phase, (2) the reorganisation phase and (3) the eruption phase. We then operationalise these three phases for different enabling innovation system functions and illustrate our observations with examples for the textile and fashion sector. We discuss how each of the three disruption phases can be accelerated to quickly create an opening for the new circular paradigm. The proposed circular disruption framework offers novel insights on socio-technical transitions and changes and contributes to strengthening a systemic and theoretically grounded approach to circular economy research. Scholars and practitioners alike may take advantage of this work to focus circular economy efforts on speed and scale—an urgently needed focus to start tackling the sustainability challenges humankind is currently facing.
Keywords: 650; circular economy; disruption; system innovation; sustainability transition; Technological Innovation Systems; urgency